Effects of Psychological Training on Competitive Fencing Outcomes - Gujarathi, Roshani Satish; Dongare, Uday Parmeshwar (MultiTech Publisher, 2024)
This study assesses how psychological training affects Fencing competition results, with a particular emphasis on improving cognitive skills and overall performance. Psychological techniques like stress reduction, mindfulness, and visualization have been shown to help with decision-making, focus, and emotional regulation in a variety of sports, including Fencing. Twenty fencers, ages 17 to 20, participated in the study and completed a six-month psychological training course. The findings show that psychological training greatly improves competitive performance as measured by improved response times, win/loss ratios, and psychological evaluations. These results support earlier studies and imply that regular athletic preparation can greatly benefit from the inclusion of psychological training. The brief training period and small sample size are limitations that call for additional research on long-term effects and a variety of participant groups.